2018
DOI: 10.1038/s41598-018-26381-w
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29c reduces the cisplatin resistance of non-small cell lung cancer cells by negatively regulating the PI3K/Akt pathway

Abstract: In previous studies, miR-29s showed tumor suppressor properties against lung cancer, which improved the survival of patients upon the administration of chemotherapy via an unknown mechanism. Here, we investigated the regulatory effects of miR-29s on the cisplatin resistance of NSCLC cells. The expression of miR-29s was assessed in 130 clinical patients and in cisplatin-treated NSCLS cell lines. MiR-29c expression was decreased in 77% of NSCLC patients. Cisplatin treatment increased the expression of miR-29c an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Hypoxia is a condition of low oxygen tension occurring in solid tumor microenvironment, associated with malignant tumor aggressiveness, and we have previously shown it to be an independent prognostic factor in NB, negatively correlating with tumor outcome [64]. MiR-29c is also a tumor-suppressor miRNA: its expression enhanced the sensitivity of non-small cell lung cancer cells to cisplatin by targeting the PI3K/Akt pathway [65]. Let-7b belongs to the let-7 family, a group of tumor suppressor miRNAs, implicated in numerous cancers, including NB.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a condition of low oxygen tension occurring in solid tumor microenvironment, associated with malignant tumor aggressiveness, and we have previously shown it to be an independent prognostic factor in NB, negatively correlating with tumor outcome [64]. MiR-29c is also a tumor-suppressor miRNA: its expression enhanced the sensitivity of non-small cell lung cancer cells to cisplatin by targeting the PI3K/Akt pathway [65]. Let-7b belongs to the let-7 family, a group of tumor suppressor miRNAs, implicated in numerous cancers, including NB.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor associated pathways, such as Wnt, PI3K/AKT or NF-kB, may play an important role in the development of tumorigenesis [24][25][26][27][28][29][30]. Further, there is increasing evidence that typical MPAK/ERK signaling pathway is a pivotal signaling pathway involved in the development of several cancers [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…[4052]. It has been reported that high miR-29c expression increased the sensitivity of non-small cell lung cancer (NSCLC) cells to the cisplatin [53]. Wang et al found that miR-29c overexpression might contribute to the efficacy of cisplatin in gastric cancer treatment [54].…”
Section: Discussionmentioning
confidence: 99%